Rational Asymmetric Development, Piketty and the Spirit of Poverty in Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2015)
The study extends the implications of Piketty's celebrated literature from developed countries to the nexus between developed nations and African countries by building on responses from Rogoff (2014) & Stiglitz (2014), post Washington Consensus paradigms and underpinnings from Solow-Swan & Boyce-Fofack-Ndikumana. The central argument presented is that the inequality problem is at the heart of rational asymmetric development between rich and poor countries. Piketty has shown that inequality increases when the return of capital is higher than the growth rate, because the poor cannot catch-up with the rich. We argue that, when the return of political economy (or capitalism-fuelled illicit capital flight) is higher than the growth rate in African countries, inequality in development increases and African may not catch-up with the developed world. As an ideal solution, Piketty has proposed progressive income taxation based on automatic exchange of bank information. The ideal analogy proposed in tackling the spirit of African poverty is a holistic commitment to fighting illicit capital flight based on automatic exchange of bank information. Hence, contrary to theoretical underpinnings of exogenous growth models, catch-up may not be so apparent. Implications for the corresponding upward bias in endogenous development and catch-up literature are discussed.
Keywords: B20; F35; F50; O19; O55; 330; Piketty; Inequality; Foreign aid; Capital flight; Development